The Role of Endophytic Fungi in Pest Management : A New Frontier in Biocontrol: Peran Jamur Endofit dalam Pengendalian Hama : Perbatasan Baru dalam Biokontrol - Awaal Mahmood Lafta (Universitas Muhammadiyah Sidoarjo, 2025)
The research was aimed at showing the potential of Trichoderma spp. — an effective biocontrol agent — against Fusarium root rot which has been identified from the investigation. Moreover, there was an increased size of treated plants that include 32.8 ± 2.5 cm compared to untreated plants with 25.3 ± 2.1 cm [p < 0.05] for plant height and 26.1 ± 2.2 cm vs. 18.4 ± 1.5 cm [p < 0.01] for root length along with fresh biomass of 65.7 ± 4.5 g vs. 45.2 ± 3.8 g [p < 0.01] for dry biomass and 19.3 ±1 .7 g vs .12 .4±1 .1g [p<0:01] for chlorophyll content which were respectively noted as [42 .7±3 .2 SPAD units vs .32 .5±2 .8 SPAD units p<0:01]. The colonization of Trichoderma spp in the roots of treated plants was confirmed by qPCR analysis, which demonstrated successful introduction due to lower Ct values recorded at a mean value of approximately twenty-three point one two plus or minus one point two compared against control group at thirty-six point five plus or minus one point five on average— indicating positive signals; these results underscore the capabilities held by Trichoderma spp and their potential use in different applications that promote plant growth and development. To demonstrate the potential of Trichoderma spp. as an effective biocontrol agent against Fusarium root rot, thus contributing to sustainable agricultural practices and a sure way of eradicating the menace.Highlight : Trichoderma spp. efektif menekan Fusarium Root Rot dan meningkatkan pertumbuhan tanaman. Endophytic fungi berperan sebagai agen Biocontrol dengan merangsang resistensi sistemik tanaman. qPCR membuktikan kolonisasi Trichoderma spp. dalam akar tanaman, mendukung efektivitasnya. Keywords : Endophytic Fungi, Pest Management, Biocontrol, Trichoderma spp., Fusarium Root Rot